Adoption of improved crop varieties limited biodiversity losses, terrestrial carbon emissions, and cropland expansion in the tropics - Uris Lantz C. Baldos; Alfredo Cisneros-Pineda; Keith O. Fuglie; Thomas W. Hertel (Proceedings of the National Academy of Sciences, 2025)
Research investments in crop improvements, including by national and international agricultural research centers, have made significant contributions to raising yields of staple food crops in developing countries. Although mostly intended to improve food security and rural incomes, innovations in crop production also have major implications for the environment. Building on the latest productivity estimates from historical crop improvements in developing countries and using a gridded (0.25 degrees) equilibrium model of global agriculture, we assess the impacts of improved crop varieties on cropland use, threatened biodiversity, and terrestrial carbon stocks over 1961–2015. We replicate a historical baseline and produce a counterfactual scenario which shows the impact of omitting productivity improvements from these technologies. The results show that higher crop productivity generally lowered commodity prices, which reduced incentives to expand cropland except in those areas where productivity gains outweighed price declines. The net global effect of technology adoption was to limit conversion of natural habitat to agricultural use, although it did cause cropland to expand in some areas. We estimate that adoption of improved crop varieties in developing countries saved on net 16.03 [95% CI, 12.33 to 20.89] million hectares worldwide. With more natural habitat preserved, around 1,043 [95% CI, 616 to 1,503] threatened animal and plant species extinctions were avoided over this period. In addition, net land use savings from the improved crop varieties resulted in avoided terrestrial greenhouse gas (GHG) emissions of around 5.35 [95% CI, 3.75 to 7.22] billion metric tons CO 2 equivalent retained in terrestrial carbon stocks.